PENGGUNAAN POLIGRAF (LIE DETECTOR) DALAM PEMBUKTIAN PERKARA PERSETUBUHAN ANAK - Melati, Agnada Risma; Septiningsih, Ismawati (Sebelas Maret University, 2023)
This article analyses the use of a polygraph (lie detector) in proving cases of child intercourse in decision number: 111/Pid.Sus/2020/PN Wno. The purpose of this article is to determine the suitability of using a polygraph (lie detector) in the crime of sexual intercourse with a child under the provisions of Article 184 paragraph (1) of the Criminal Procedure Code. This writing uses normative legal research methods that are prescriptive and applied. The approach used in this research is a case approach. Types and sources of legal materials through library research. The results of the study show that the use of a polygraph (lie detector) in the evidence carried out by the Public Prosecutor regarding the crime of sexual intercourse with a child in the decision number: 111/Pid.Sus/2020/PN Wno is in accordance with Article 184 paragraph (1) of the Criminal Procedure Code, namely as letter evidence. However, in this case its position is only limited as complementary evidence, not as the main evidence at trial, so it must be paired with other evidence to strengthen the evidentiary process in court. Keywords: Proof; Polygraph; Letter